Counselling Services and Mental Health for International Chinese College Students in Post-Pandemic Thailand - Huan Cao; Weixin Lin; Pengfei Chen (MDPI AG, 2022)
Research has proven that counselling services are essential to solving the troubles in the mental health of international Chinese students in the post-epidemic stage. Online questionnaires were implemented for about 1000 international Chinese college students from three universities in Thailand. Results showed that female junior and senior students who stayed in post-pandemic Thailand longer than others were likely to suffer from mental health disorders. In addition, in Thailand, counselling has a significant positive association with the mental health status of the students. Therefore, it is recommended in this study that Thai universities should provide more counselling services to support students in focusing on education and adjusting or adapting to the environment abroad.